MOTIVATIONAL FACTORS OF LEARNING ACTIVITY AMONG GIFTED STUDENTS IN SPECIALIZED SCHOOLS - Xodjayeva Dilnovoz Djumoyevna (Western European Studies, 2025)
This article investigates the motivational factors influencing learning activity among gifted students enrolled in specialized schools. The study aims to identify key intrinsic and extrinsic determinants that shape students’ engagement in learning activities under conditions of intensified academic demands. A mixed-method research design was employed, including standardized motivation scales and statistical analysis. The findings demonstrate that intrinsic motivation, achievement orientation, and self-regulation serve as dominant predictors of learning activity among gifted students, while external factors such as teacher support and the educational environment function as facilitating conditions rather than primary drivers. The results highlight the importance of creating psychologically supportive learning environments that foster autonomy and competence in gifted learners.
Keywords: learning motivation; gifted students; specialized schools